ANALISIS KAPASITAS PRODUKSI PHYLON UNTUK MENDUKUNG JADWAL INDUK PRODUKSI MENGGUNAKAN METODE ROUGH CUT CAPACITY PLANNING (RCCP) DI PT HANJIN INSOLE INDONESIA PURWAKARTA - Sandra Damayanti; Asep Hermawan; Rizky Fajar Ramdhani; Yayan Heru Haerudin (Industry Xplore, 2024)
PT Hanjin Insole Indonesia is a company that produces phylon for shoe products. PT Hanjin Insole Indonesia has two products: Airmax 270 and Airmax Dawn. The company needs to know the factory's capacity to meet consumer demand. The main factor causing the company to be unable to meet consumer demand is that demand in each period experiences unstable conditions, which results in it being unable to meet demand. The company needs to do production planning to predict demand and ensure that consumer needs are met on time. By using the forecasting method, the company can determine the demand needed. The Aggregate Production Plan is designed to manage the costs required. The Master Production Schedule allows the company to evaluate its production capabilities and anticipate changes in demand each period. At the same time, Rough Cut Capacity Planning helps assess the company's capacity to meet demand. This study shows that the required production capacity has not reached the available capacity, with a percentage of 77% of the company's capacity, so the master production schedule for next year is considered adequate and has the potential to be maximized.